(untitled) (The Pakistan Development Review, 2000)
Income distribution entered the post war discussion of economic development fairly late. Until the 1960s much of the focus was on industrialisation and the need for capital accumulation. Pakistan was no exception as in the early 60s economic expansion became the main target and means to political identity. Rapid population growth associated with steep decline in mortality demanded acceleration of production to keep pace. Overall aggregate expansion was much faster than before but without benefit for the poor. In that context emerged a new professional interest in income distribution. Haq’s (1964) study was one of the oldest studies conducted to measure inequality in personal income distribution in the high income brackets in the urban areas of Pakistan. The main objective of the author was to present the income distribution pattern in terms of the relative shares of different income groups as well as in terms of Pareto coefficients and concentration ratio during the period 1948-49 to 1957-58 for which published tax data was available. While recognising the limitations of the data used, the author went on to calculate various measures of income inequality including Pareto coefficient and Lorenz curve. The author also made comparison of Pakistan’s income distribution with U.S.A. and U.K.